Oolemma Invagination of Fresh and Cryopreserved Human Oocytes During in Vitro Fertilization by ICSI - Petrushko, Maryna P.; Yurchuk, Taisiia O.; Buderatska, Natalia O.; Piniaiev, Volodymyr I. (Problems of Cryobiology and Cryomedicine, 2018)
Development of novel prognostic criteria for evaluation in vitrofertilization of fresh and cryopreserved oocytes is an important component of modern assisted reproductive technologies. There was compared a degree of oolemma invagination during intracytoplasmic sperm injection into fresh and cryopreserved oocytes. The classification of the gamete turgor state based on oolemma degree invagination during intracytoplasmic sperm injection was developed. This behavior of oocyte membrane is a prognostic characteristic of zygotic formation rate. Oocytes with normal turgor were characterized by a high fertilization rate higher than 80%. Immediate oolemma puncture during oocyte micromanipulation showed structural and functional damage of membrane and led to further oocyte degeneration. After cryopreservation by a standard method the ratio of different types of oolemma invagination has been changed. A relative number of cells with normal turgor was decreased down to 54% due to an increase of oocyte number with higher membrane elasticity. The four-stage method of cryoprotective media removing after oocyte freeze-thawing is more effective for preserving gametes with normal turgor contrary to the standard two-stage one. Â  Probl Cryobiol Cryomed 2018; 28(3): 258â€“265